2006
DOI: 10.1063/1.2266930
|View full text |Cite
|
Sign up to set email alerts
|

Manganese impurities in boron nitride

Abstract: Effects of nitrogen vacancies on transition-metal-doped GaN: An ab initio studyManganese-induced long-range lattice disorder and vacancy formation in metal-organic chemical vapor deposition grown and ion-implanted Ga 1 − x Mn x N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…All those approximations and convergence criteria have been shown to provide an accurate description of several defect centers in semiconductors. 32,33 The formation energy of a complex in a q charge state ͑E f q ͒ was computed by…”
Section: Methodsmentioning
confidence: 99%
“…All those approximations and convergence criteria have been shown to provide an accurate description of several defect centers in semiconductors. 32,33 The formation energy of a complex in a q charge state ͑E f q ͒ was computed by…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that TMs occupy both substitutional and center-bond sites in Ge. 26 Assali and co-worker 27 also found that Mn is energetically more favorable in a divacancy site as compared to the B site in boron nitride (BN) and forms splitvacancy defects. In SiC, it is not clear if the 4d and 5d TMs with larger ionic radii prefer the Si site to form isolated substitutional defects or a split-vacancy site as in BN.…”
Section: Nbmentioning
confidence: 99%
“…[18]. In order to get that, we considered an alignment of the RE 5d-related energy levels, according to the average energy of spin up and down states.…”
Section: (B)mentioning
confidence: 99%
“…is the smallest atomic sphere radius. All those approximations provide a reliable description on the electronic and structural properties of several impurity centers in semiconductors [17][18][19][20].…”
mentioning
confidence: 99%
See 1 more Smart Citation